Surveillance cattle diseases using embedded application systems - Zhang,J; Calvo,R; Shephard,R; Jin,C (Wseas Transactions on Information Science and Applications, 2007)
Veterinary disease surveillance systems are rapidly expanding and developing. A key factor for success of a surveillance system is the ease of data capture. Real-time collection of observations of diseased cattle is difficult because observations occur in the field. This paper presents a mobile embedded application system for reporting cattle disease observations to a veterinary surveillance system in real-time. The mobile system includes an artificial intelligence system and supports data extraction via a user-friendly interface. This allows users to investigate and report cattle disease in the field and is designed to deliver benefits to producers, government surveillance systems and to the cattle industry.